'Context is everything … ': Ruminations on Developments in the History of Cartography since the 1970s and Their Consequences. Issue Volume 72:Issues 2(2020) (2nd July 2020) - Barber, Peter
: Note from the Editor: The following article incorporates the text of the first of the two keynote addresses initiating formal proceedings at the 2019 Conference on the History of Cartography. In view of its historiographical interest, the Editor invited Peter Barber, a former Head of Maps at the British Library and an authority on divers aspects of map history, to share his reflections with readers of this Journal. Although the spoken text has had to be abbreviated in places, some further, post-Conference, observations have been added.